The relationship between dementia staging scales, cognitive-behavioral scales and functionality in patients with cognitive impairment - Fatma Ozge Kayhan Koçak; Emre Kumral (PLoS ONE, 2025)
Introduction The aim of this study is to retrospectively evaluate the relationship between dementia stage, cognitive and behavioral scales, and functional status in patients with cognitive impairment. Methods The medical records of patients over 50 years of age, who were followed up for cognitive impairment at the neurology outpatient clinic were retrospectively scanned between January 1990 and November 2022. The Clinical Dementia Rating (CDR), Global Deterioration Scale (GDS) and Functional Assessment Staging Test (FAST), The Mini Mental State Examination (MMSE) and the Alzheimer’s Disease Assessment Scale-Cognitive Subscore (ADAS-Cog) were recorded. The neuropsychiatric symptoms were evaluated by the Neuropsychiatric Inventory (NPI) and The Behavioral Pathology in Alzheimer’s Disease Rating Scale (BEHAVE-AD). Patients’ Instrumental Assessment of Daily Living (IADL) scores were recorded to assess functional capacity. Results This study analyzed 871 patients with cognitive impairment, 69.8% of whom were having functional impairment. Alzheimer’s disease was the most common type of dementia (64.6%), with memory problems as the key symptom (65.6%). Neuropsychiatric symptoms such as hallucinations, delusion, and eating disturbances were significantly associated with disability (p < 0.001), while depression and anxiety were not. CDR scale was the strongest predictor of disability (OR: 4.9, AUC = 0.740), outperforming other dementia staging scales. Cognitive and behavioral scales like MMSE and NPI showed stronger correlations with functional impairment than with the dementia staging scales (-0.132 < rs < 0.472, p < 0.001 and -0.284 < rs < -0.357, p < 0.001, respectively). Conclusion Our study demonstrated that both cognitive status and behavioral symptoms are critical in determining the level of functional impairment in cognitive impairments, but their contributions differ in magnitude and focus. As well as cognitive decline, neuropsychiatric symptoms may also need targeted management to reduce their impact on functionality. We need a practical tool that can be used in all stages of dementia, that does not overlook the impact of neuropsychological symptoms, and that can assess ADL according to the needs of patients and carers.